Correlations Between Intestinal Microbial Community and Hematological Profile in Native Tibetans and Han Immigrants - Ma, Yan; Ga, Qin; Ge, Ri-Li; Ma, Shuang (Frontiers in Microbiology, 2021)
Hematological features are one of the best-known aspects of high-altitude adaptation in Tibetans. However, it is still unclear whether the intestinal microbiota is associated with the hematology profile. In this study, routine blood tests and 16S rRNA gene sequencing were used to investigate the differences in the intestinal microbiota and hematological parameters of native Tibetan herders and Han immigrants sampled at 3900 m. The blood test results suggested that the platelet counts were significantly higher in native Tibetans than the Han immigrants. The feces of the native Tibetans had significantly greater microbial diversity (more different species: simpson’s and shannon’s indices) than that of the Han immigrants. The native Tibetans also had a different fecal microbial community structure than the Han immigrants. A Bray-Curtis distance-based redundancy analysis and envfit function test showed that body mass index (BMI) and platelet count were significant explanatory variables that correlated with the fecal microbial community structure in native Tibetans. Spearman’s correlation analysis showed that Megamonas correlated positively with BMI, whereas Bifidobacterium correlated negatively with BMI. Alistipes and Parabacteroides correlated positively with the platelet count. Succinivibrio correlated positively with SpO2. Intestinibacter correlated negatively with the red blood cell count, hemoglobin and hematocrit (HCT). Romboutsia correlated negatively with HCT, whereas Phascolarctobacterium correlated positively with HCT. A functional analysis showed that the functional capacity of the gut microbial community in the native Tibetans was significantly related to carbohydrate metabolism and genetic information processing. Together, these findings suggest that the hematological profile is associated with the fecal microbial community, which may influence the high-altitude adaptation/ acclimatization of Tibetans.